Licit Substance Use in Physical Rehabilitation Settings - McArthur, Brynne; Campbell, Alexandra; Bianchi, Andria (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2022)
The purpose of this commentary is to consider circumstances under which it may be ethical to permit patients to use licit substances in rehabilitation contexts. While the content of this commentary may be transferable to other healthcare spaces, our focus on rehabilitation is based on some important distinctions that exist between rehabilitation and acute care spaces.